2008
DOI: 10.2215/cjn.02760608
|View full text |Cite
|
Sign up to set email alerts
|

Opportunity™

Abstract: Background: The mortality rate of maintenance hemodialysis (MHD) patients remains high. Measures of protein-energy wasting, including hypoalbuminemia, are strongly associated with their high mortality. Growth hormone (GH) may improve lean body mass (LBM) and serum albumin levels, and health-related quality of life (HRQoL), which are significantly and positively associated with survival in MHD patients. The OPPORTUNITY TM Trial will examine whether GH reduces mortality and morbidity and improves overall health … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 60 publications
1
22
0
Order By: Relevance
“…These findings are consistent with reports demonstrating that dialysis patients with laboratory evidence of malnutrition and/or inflammation have low levels of physical activity, higher fatigue and mortality [1,2,8,26]. Perhaps improving nutrition or increasing albumin levels by pharmacological interventions [27] in these patients will improve not only quantity but also quality of life by reducing fatigue.…”
Section: Discussionsupporting
confidence: 89%
“…These findings are consistent with reports demonstrating that dialysis patients with laboratory evidence of malnutrition and/or inflammation have low levels of physical activity, higher fatigue and mortality [1,2,8,26]. Perhaps improving nutrition or increasing albumin levels by pharmacological interventions [27] in these patients will improve not only quantity but also quality of life by reducing fatigue.…”
Section: Discussionsupporting
confidence: 89%
“…The sleep disorder cause to fatigue has been hypothesized through two mechanisms: excessive daytime sleepiness and increased level of certain inflammatory cytokines. 35 Our finding suggests that fatigue significantly related to the self-reported sleep quality. Measures to relieve sleep disorder may decrease fatigue and perhaps improve these people's quality of life, functional health status, and outcome.…”
Section: Discussionmentioning
confidence: 52%
“…Prior studies have shown that serum albumin levels <4.0 g/dL are predictive of higher death risk in hemodialysis patients, and that even mild increases in serum albumin of !0.2 g/dL over time are associated with improved survival, lower hospitalization risk, and reduced treatment costs [19][20][21]24]. While the degree to which a decline in serum albumin reflects protein-energy wasting, increased protein catabolism, dialytic protein and amino acid losses and inflammation in these studies remains unclear, large observational studies show that moderate increases in protein intake are also associated with greater survival compared to reductions in protein intake in this population.…”
Section: Discussionmentioning
confidence: 99%
“…This serum albumin threshold was selected according to prior data demonstrating associations with lower mortality, hospitalization risk and treatment costs in hemodialysis patients [19][20][21]. Secondary outcomes included (i) achievement of the individual endpoints of the primary composite outcome, (ii) change in chronic kidney disease-mineral and bone disease biochemical parameters [serum calcium, parathyroid hormone (PTH), alkaline phosphatase], (iii) change in nPCR, (iv) change in serum electrolytes that correlate with protein intake (serum bicarbonate, potassium), (v) change in …”
Section: Study Outcomesmentioning
confidence: 99%